JEMPUT BOLA TERPADU: (SEBUAH ANALISIS STRATEGI OPTIMALISASI LAYANAN ADMINDUK DI KABUPATEN SIDOARJO) - Suwandi, Rossi Maharani; Meirinawati, Meirinawati (Universitas Negeri Surabaya, 2024)
The Sidoarjo Regency Population and Civil Registry Department created an integrated pick-up and drop-off service as an effort to optimize population administration services, create orderly administration and increase the scope of ownership of population documents. JBT Sayang is a superior and regular service. However, in its implementation, JBT Sayang experienced several obstacles such as a lack of socialization regarding the required requirements, network problems and limited service time. This research aims to analyze and describe the JBT Sayang service as a strategy for optimizing population administration services in Sidoarjo Regency. This research uses descriptive research methods with a qualitative approach. The research focus is based on the strategic management process theory according to Ramli and Kartini which includes identification of vision and mission, internal and external analysis, strategy formulation, strategy implementation, evaluation and control. The data in the research was obtained through observation, interviews and documentation. The data analysis techniques in this research are data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the Sidoarjo Regency Population and Civil Registration Department has made maximum efforts to implement the JBT Sayang service through its strengths, namely organizational structure, organizational culture, competent human resources and a program designed as an integrated service. The implementation of the JBT Sayang service carried out by Dispendukcapil has been appropriate so that there has been an increase in ownership of population documents in Sidoarjo Regency. However, there are obstacles such as a lack of staff, limited facilities and infrastructure, the applicant's character/mindset and lack of detailed information dissemination by the village government. Suggestions that can be given are: completing facilities and infrastructure, improving the socialization system, seeking additional staff, and further involving the role of village government as a medium for disseminating information.